The impact of investment in industrial cities on economic development indicators in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This study aimed to identify the extent to which Syrian industrial cities contribute to advancing economic development by attracting Arab and foreign investments, demonstrating their impact on the gross domestic product, and creating job opportunities for the workforce to reduce the problem of unemployment.This study was carried out in a group of Syrian industrial cities: the industrial city of Adra (Damascus), the industrial city of Sheikh Najjar (Aleppo), and the industrial city of Hasiya (Homs).In the beginning, some literature related to the research was studied to obtain a deep understanding of the problem. The size of investments in industrial cities and the extent of their impact on reducing unemployment was defined. The most important statistical methods for the study were pointed out, and some statistical methods were summarized by relying on appropriate statistical tools such as correlations and analysis of variance.In the beginning, some literature related to the research was studied to obtain a deep understanding of the problem. The size of investments in industrial cities and the extent of their impact on reducing unemployment was defined. The most important statistical methods for the study were pointed out, and some statistical methods were summarized by relying on appropriate statistical tools such as correlations and analysis of variance.في البداية تمت دراسة بعض المؤلفات المتعلقة بالبحث للحصول على فهم عميق للمشكلة. وتم تحديد حجم الاستثمارات في المدن الصناعية ومدى تأثيرها في الحد من البطالة. وتم الإشارة إلى أهم الأساليب الإحصائية للدراسة، كما تم تلخيص بعض الأساليب الإحصائية بالاعتماد على الأدوات الإحصائية المناسبة مثل علاقات الارتباط وتحليل التباين.In the beginning, some literature related to the research was studied to gain a deep understanding of the problem. The size of investments in industrial cities and the extent of their impact on reducing unemployment was defined. The most important statistical methods for the study were pointed out, and some statistical methods were summarized by relying on appropriate statistical tools such as correlations and analysis of variance.في البداية تمت دراسة بعض المؤلفات المتعلقة بالبحث للحصول على فهم عميق للمشكلة. وتم تحديد حجم الاستثمارات في المدن الصناعية ومدى تأثيرها في الحد من البطالة. وتم الإشارة إلى أهم الأساليب الإحصائية للدراسة، كما تم تلخيص بعض الأساليب الإحصائية بالاعتماد على الأدوات الإحصائية المناسبة مثل علاقات الارتباط وتحليل التباين.يتعذّر تحميل النتائج بالكامل.إعادة المحاولةجارٍ إعادة المحاولة...And index numbers and time series with the help of appropriate statistical programs. The most important results of this study were: 1- The volume of investments in the industrial cities studied separately is linked to the gross domestic product in Syria with a first-degree linear regression relationship. 2- The volume of investments is linked to the unemployment rate.And index numbers and time series with the help of appropriate statistical programs. The most important results of this study were: 1- The volume of investments in the industrial cities studied separately is linked to the gross domestic product in Syria with a first-degree linear regression relationship. 2- The volume of investments is linked to the unemployment rate.والأرقام القياسية والسلاسل الزمنية بالاستعانة بالبرامج الإحصائية المناسبة. وكانت أهم نتائج هذه الدراسة ما يلي: 1- يرتبط حجم الاستثمارات في المدن الصناعية المدروسة بشكل منفصل بالناتج المحلي الإجمالي في سورية بعلاقة انحدار خطي من الدرجة الأولى. 2- يرتبط حجم الاستثمارات بمعدل البطالة.And index numbers and time series with the help of appropriate statistical programs. The most important results of this study were: 1- The volume of investments in the industrial cities studied separately is linked to the GDP in Syria with a first-degree linear regression relationship. 2- The volume of investments is linked to the unemployment rate.والأرقام القياسية والسلاسل الزمنية بالاستعانة بالبرامج الإحصائية المناسبة. وكانت أهم نتائج هذه الدراسة ما يلي: 1- يرتبط حجم الاستثمارات في المدن الصناعية المدروسة بشكل منفصل بالناتج المحلي الإجمالي في سورية بعلاقة انحدار خطي من الدرجة الأولى. 2- يرتبط حجم الاستثمارات بمعدل البطالة.يتعذّر تحميل النتائج بالكامل.إعادة المحاولةجارٍ إعادة المحاولة...In Syria, there is a first-degree linear regression relationship.